Methods For Evaluation Of The Education Quality In Higher Education Institutions - I. Y., Anikin; S. V., Lapteva; A. V., Kozlov (The journal of contemporary issues in business and government, 2021)
The article aims to disclose the essence of the “education quality” concept, to study the international approaches and concepts of the higher education quality evaluation, to analyze specific methods and tools within one of the approaches. Establishing education quality assessment necessitates choosing the teaching personnel of higher educational institution, as well as a target group of students and independent experts in the field of organization of the educational process, on a distance basis particularly. Monitoring requires using such methods as interviews, surveys, questionnaires, and similar. The results were processed according to the authors’ algorithm allowing to calculate the quality of education. The authors’ interpretation of the concept of “education quality” is proposed. Given the insufficient study of the topic of distance education in the domestic scientific discourse, authors’ attention to this problem is an important contribution to study of the issue of distance education. The methods used to evaluate the education quality in higher education institutions at the international level are an integral element in the development of the educational space, although they cause certain controversy and criticism. The authors advise to select the methods for evaluating the educational process quality with account of the specific evaluation stage and purpose.